(untitled) (Nóema, 2012)
The author contends that the prevailing mode of thinking in a technically advanced society is aineed at measuring with a clearcut precision specific phenomena while the involontary thinking as contemplation is being blurred. Electronic mass media of communication tend to enhance such tendency Media do not mediate. Information, as rich as it might be, risks to become deformation.